2019
DOI: 10.1194/jlr.m094607
|View full text |Cite
|
Sign up to set email alerts
|

Efficient reabsorption of transintestinally excreted cholesterol is a strong determinant for cholesterol disposal in mice

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 54 publications
2
26
0
Order By: Relevance
“…Anti-steatotic effects of ASBT pharmacological inhibition have been a consistent finding in high fat diet-fed mouse models, including the CSAA diet-fed mice in this study (10,11), and we previously observed inhibitory effects of ASBT genetic inactivation on intestinal cholesterol and fat absorption (29,34,35). In our current study, ASBTi treatment lowered fatty acid absorption and intestinal fat absorption positively correlated with hepatic triglyceride levels in the CSAA diet-fed mice.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Anti-steatotic effects of ASBT pharmacological inhibition have been a consistent finding in high fat diet-fed mouse models, including the CSAA diet-fed mice in this study (10,11), and we previously observed inhibitory effects of ASBT genetic inactivation on intestinal cholesterol and fat absorption (29,34,35). In our current study, ASBTi treatment lowered fatty acid absorption and intestinal fat absorption positively correlated with hepatic triglyceride levels in the CSAA diet-fed mice.…”
Section: Discussionsupporting
confidence: 87%
“…Inhibiting the ASBT in mice has been shown to increase the proportion of cholic acid (CA) plus its bacterial dehydroxylation product deoxycholic acid (DCA) and to reduce the proportion of 6-hydroxylated bile acid species, including alpha-muricholic acid (αMCA), beta-muricholic acid (βMCA), and the bacterial product omega-muricholic acid (ωMCA) (10,11,29). To determine if the CDAA diet alters the effect of ASBT inhibition on bile acid composition, the fecal bile acid profiles were determined using quantitative three-day fecal collections performed for individually-housed mice (Figure 2).…”
Section: Asbt Inhibitor Treatment Reduces Bodyweight Gain In Csaa Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Interruption of the enterohepatic circulation of BAs by inhibition or genetic inactivation of the apical sodium-dependent BA transporter (ASBT, SLC10A2) in mice decreased intestinal lipid absorption. [9][10][11] Micellar solubilization is most important for hydrophobic lipids such as cholesterol, fat-soluble vitamins, and (long-chain) saturated fatty acids (SFAs). Studies using cholestatic and bile-deficient rat models showed more pronounced effects on absorption of long chain SFAs than on long chain PUFAs.…”
Section: Introductionmentioning
confidence: 99%
“…[12,13] ASBT deficiency, however, not only decreases total BA concentrations, but also shifts the BA composition towards a more hydrophobic profile containing more cholic acid (CA) and less muri-cholic acid (MCA). [9,11,14] Hydrophobic BAs have a lower CMC and are more efficient in micellar solubilization. [15,16] Therefore, it was hypothesized that the increase in biliary hydrophobicity relatively preserves lipid absorption in Asbt −/− mice.…”
Section: Introductionmentioning
confidence: 99%